Antibiotic appropriateness and guideline adherence in hospitalized children: results of a nationwide study. (7th November 2019) - McMullan, Brendan J; Hall, Lisa; James, Rodney; Mostaghim, Mona; Jones, Cheryl A; Konecny, Pamela; Blyth, Christopher C; Thursky, Karin A
Abstract: Background: Information on the nature and appropriateness of antibiotic prescribing for children in hospitals is important, but scarce. Objectives: To analyse antimicrobial prescribing and appropriateness, and guideline adherence, in hospitalized children across Australia. Patients and methods: We analysed data from the National Antimicrobial Prescribing Survey (NAPS) from 2014 to 2017. Surveys were performed in hospital facilities of all types (public and private; major city, regional and remote). Participants were admitted children <18 years old. Risk factors associated with inappropriate prescribing were explored using logistic regression models. Results: Among 6219 prescriptions for 3715 children in 253 facilities, 19.6% of prescriptions were deemed inappropriate. Risk factors for inappropriate prescribing included non-tertiary paediatric hospital admission [OR 1.37 (95% CI 1.20–1.55)] and non-major city hospital location [OR 1.52 (95% CI 1.30–1.77)]. Prescriptions for neonates, immunocompromised children and those admitted to an ICU were less frequently inappropriate. If a restricted antimicrobial was prescribed and not approved, the prescription was more likely to be inappropriate [OR 12.9 (95% CI 8.4–19.8)]. Surgical prophylaxis was inappropriate in 59% of prescriptions. Conclusions: Inappropriate antimicrobial prescribing in children was linked to specific risk factors identified here, presenting opportunities for targeted interventions to improve prescribing. This information, using a NAPS dataset, allows for analysis of antimicrobial prescribing among different groups of hospitalized children. Further exploration of barriers to appropriate prescribing and facilitators of best practice in this population is recommended.